2015
DOI: 10.1002/cne.23822
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral lesions in a specific subregion of posterior insular cortex impair conditioned taste aversion expression in rats

Abstract: Gustatory cortex (GC) is widely regarded for its integral role in the acquisition and retention of conditioned taste aversions (CTAs) in rodents, but large lesions in this area do not always result in CTA impairment. Recently, using a new lesion mapping system, we found severe CTA expression deficits were associated with damage to a critical zone that included the posterior half of GC in addition to the insular cortex (IC) that is just dorsal and caudal to this region (visceral cortex). Importantly, lesions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 58 publications
2
43
2
Order By: Relevance
“…Lesioning of the anterior IC, a structure heavily implicated in integration of interoceptive cues of stimuli, particularly drugs of abuse (Naqvi and Bechara, 2010) results in interference with the acquisition of CTA induced by drugs of abuse, but not LiCl, remarkably similar to the results observed here (Geddes et al, 2008; Mackey et al, 1986; Zito et al, 1988). Acquisition of LiCl-induced CTA is dependent on relatively more caudal areas of the IC (Schier et al, 2016; Schier et al, 2014). Nicotine administered to the anterior IC increases GABAergic tone and ultimately results in a depression of synaptic potentiation (Sato et al, 2017), primarily at layer 5-pyramidal neurons, the primary excitatory output of the IC.…”
Section: Discussionmentioning
confidence: 99%
“…Lesioning of the anterior IC, a structure heavily implicated in integration of interoceptive cues of stimuli, particularly drugs of abuse (Naqvi and Bechara, 2010) results in interference with the acquisition of CTA induced by drugs of abuse, but not LiCl, remarkably similar to the results observed here (Geddes et al, 2008; Mackey et al, 1986; Zito et al, 1988). Acquisition of LiCl-induced CTA is dependent on relatively more caudal areas of the IC (Schier et al, 2016; Schier et al, 2014). Nicotine administered to the anterior IC increases GABAergic tone and ultimately results in a depression of synaptic potentiation (Sato et al, 2017), primarily at layer 5-pyramidal neurons, the primary excitatory output of the IC.…”
Section: Discussionmentioning
confidence: 99%
“…Our data reveal that innocuous taste experience specifically affects processing of the association between taste and malaise in gustatory cortex (GC on the processing of a new taste (sucrose, see below) or nausea alone. We also found no significant differences in the expression of c-Fos across the anterior to posterior axis of the structure, suggesting that, while distinct sub-divisions of GC may contribute differently to CTA memory itself (Schier et al 2016), TPE affects learning-related activity uniformly across the entirety of GC.…”
Section: Discussionmentioning
confidence: 59%
“…However, gustatory cortex is multisensory, responding to tactile, temperature, auditory, and odor stimuli (Samuelsen et al, 2012, 2013; Samuelsen and Fontanini, 2017; Stapleton et al, 2006; Verhagen et al, 2004) suggesting it to be the first region capable of integrating taste and odor signals (Small, 2012). Research has shown that gustatory cortex mediates taste and odor experience-dependent behaviors, including conditioned taste aversion (Roman and Reilly, 2007; Schier et al, 2016), taste-potentiated odor aversion (Lin et al, 2009a), taste neophobia (Koh et al, 2003; Lin et al, 2012, 2009b) and odor-taste associations (Schul et al, 1996). Here, we add to these works showing experience-dependent differences in gustatory cortex to taste, odor and odor-taste stimuli.…”
Section: Discussionmentioning
confidence: 99%